Diurnal cycle of linear contrails, cirrus, and outgoing longwave radiation in the North Atlantic from MODIS, MSG and models - Graf, Kaspar; Schumann, Ulrich; Minnis, Patrick; Duda, David (2014)
Cloud cover from linear contrails, cirrus cloud cover, and outgoing longwave radiation (OLR) at top of the atmosphere were derived from MSG SEVIRI in a North Atlantic region (NAR) for a period of eight years (Febr 2004- Jan 2012) with 15 min time resolution. The aviation induced contributions to cirrus coverage and OLR in the NAR flight corridor were derived from these data assuming linear response of cirrus and OLR changes to air traffic density and cirrus/OLR background without aviation assumed either constant of as observed in the corresponding South Atlantic region (SAR). Global results were obtained by extrapolating the regional results with global models [Graf et al., 2012; Schumann and Graf, 2013]. Here, the results are compared with linear contrail coverage values derived from MODIS aboard the LEO satellites Terra and Aqua [Duda, Minnis et al., 2013] . The global observations revealed surprisingly high contrail cover in the North Atlantic region. Terra and Aqua overpass times in the NAR are limited to four narrow time intervals and hence cannot resolve the full diurnal cycle. The results are also compared with predictions of contrail cover and OLR forecast by the Contrail and Cirrus Prediction tool CoCiP. CoCiP computes the cirrus and OLR changes for given meteorology and given air traffic. The comparisons show that the LEO observations tend to overestimate the daily mean aviation effects in the NAR because the observations times coincide with times of traffic peaks in the NAR.